Propriedades termofísicas e de agregação de líquidos iônicos dianiônicos derivados de ácidos carboxílicos - Kuhn, Bruna Luiza (2020)
Ionic Liquids (ILs) have been considered good candidates for thermal storage materials due to their properties of thermal stability, non-flammability, low volatility, low corrosion and high heat capacity. Dicationic ILs imidazolium-based with bromide anions perform better than their monocationic analogues, however these ILs have high toxicity. Considering that alkylcarboxylate anions have high heat capacity and low toxicity, this Thesis presents the synthesis, characterization, study of the thermophysical properties of dicationic ionic liquids (ILs) derived from imidazole ([Cn(MIM)2]2+, n = 4, 6 , 8, 10 carbons in the spacer chain) with anions derived from dicarboxylic acids (oxalic, malonic, succinic, glutaric, adipic and pimelic acids) for thermal storage. ILs were characterized by 1H and 13C nuclear magnetic resonance (NMR), mass spectrometry, infrared, thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC). Thermogravimetric analysis showed that dicarboxylate ILs have thermal stability between 200 - 249 °C and are less stable than their mono- and dicationic analogues with bromide anions. The LIs [C4(MIM)2][Oxa], [C6(MIM)2][Mal], [C6(MIM)2][Adi], [C4(MIM)2][Pim], [C8(MIM)2][Oxa], [C8(MIM)2][Suc], [C10(MIM)2][Oxa] and [C10(MIM)2][Pim] presented crystalline and amorphous structural organization represented by melting point and glass transition (Tg) and the other LIs were totally amorphous. For ILs that exhibited crystalline organization, the heat of fusion increased with the increase in the size of the dication spacer chain. The size of the anion spacer chain did not affect the heat of fusion. The dicarboxylate ILs showed higher heat capacities than monocationic ILs imidazolium-based with bromide anions, but lower in relation to their dicationic analogues with bromide anions. The dicarboxylate ILs showed thermal storage densities (Es) lower than their dicationic analogues derived from imidazole with bromide anions. However, [C6(MIM)2][Mal] and [C6(MIM)2][Pim] showed Es greater than thermal oils commonly used as heat storage materials. All the dicarboxylate ILs studied were soluble in polar protic solvents and in dimethyl sulfoxide. In turn, applications of ILs in solution, particularly applications that depend on the formation of nano-organized structures, such as micelles, depend on studies of the relationship between the structure of the IL and the formation of supramolecular aggregates in solution. Thus, this Thesis also presents a study of the aggregation behavior in aqueous solution of dicationic dicarboxylate ILs with dications [Cn(MIM)2]2+ with n = 8 and 10 carbons in the spacer chain. Electrical conductivity and 1H NMR techniques were used. The results showed that dicarboxylate ILs aggregated more easily than their mono- and dicationic analogues imidazolium-based with a bromide anion. It was not possible to correlate the influence of the dianion spacer chain with the obtained CMC values. Based on the shielding and deshielding behaviors observed for the dication and dianion nuclei, a model of supramolecular self-organization for the formed micelles was proposed. Due to the shielding effect suffered by all the hydrogens of the evaluated dianions, it was proposed that the spacer chain would be oriented in order to interact with the hydrophobic chain of the dication, and the dicarboxylate portions would be interacting with the hydrophilic heads of the dication